DDIS-15. A NOVEL DOPAMINE RECEPTOR 3 ANTAGONIST INHIBITS THE GROWTH OF PRIMARY AND TEMOZOLOMIDE RESISTANT GLIOBLASTOMA CELLS. (5th November 2018) - Scott, Sarah; Libby, Catherine; Hjelmeland, Anita
Abstract: Glioblastoma (GBM) is the most common, lethal primary adult brain tumor with patient survival of only 14 months. The location and invasion of GBM leads to rapid recurrence after therapy. The standard of care chemotherapy is DNA damaging agent temozolomide (TMZ), to which resistance is common and is due, partly, to expression of the DNA repair enzyme O-6-methylguanine-DNA methyltransferase(MGMT), regulated by promoter methylation. To improve treatment of GBMs, including those resistant to TMZ, we explored targeting dopamine receptor signaling. Prior reports indicated roles for dopamine receptor 2 and 4 in GBM, with these inhibitors being effective in combination with EGFR inhibitors or temozolomide, respectively. We demonstrate that dopamine receptor 3 (DRD3) is an alternative target for therapy, with an expected low risk of severe side effects due to restricted expression in non-tumor brain. Six novel antagonists of DRD3 decreased the growth of GBM xenograft-derived neurosphere cultures, with minimal toxicity against human astrocytes and neurons. For those compounds, with a potential therapeutic window, two (SRI-21979 and SRI-30052) readily crossed the BBB and yielded no signs of liver or kidney dysfunction. In orthotopic models, 10 mg/kg of SRI-21979 per day for ten days, alone or combined with TMZ, trends toward increased survival. In striking contrast, we observed no benefit for haloperidol treatment in combination with TMZ beyond that for TMZ alone. Further analysis of TCGA data demonstrated that, unlike DRD2 and DRD4, DRD3 levels were not reduced in MGMT unmethylated GBMs and higher levels of DRD3 were associated with worse prognosis, suggesting that DRD3 antagonists may remain efficacious in TMZ resistant GBMs. SRI-21979, but not haloperidol or TMZ, significantly reduced the growth of TMZ resistant U251 cells and neurospheres derived from a TMZ-resistant xenograft. Our data demonstrate that DRD3 antagonist based combinatorial therapies may provide a potential, novel therapeutic treatment for GBM.